Interpreting destination image through theory building approach / Noraminin Khalid - Khalid, Noraminin (Institute of Graduate Studies, UiTM, 2018)
This qualitative study is an exploratory attempt at understanding destination image through the writings of the travel writers who have undergone the FAMiliarisation or FAM programs organised by Tourism Malaysia. The idea behind the program is for the writers to experience first hand specific destinations in Malaysia and then share their experiences through their travel writings. The main focus was the content of the articles or themes of particular magazines and their writings represented endorsed information. The data in the form of the travel articles (FAM articles) were collected with the assistance of Tourism Malaysia based on the suggested criteria established. FAM articles were collected for analyses representing writers from several countries including Australia, Canada, Brunei Darussalam, USA, United Kingdom and India to name a few. Using the qualitative method of content analysis and adapting the coding procedures of open, axial and selective codings from the grounded theory approach, this study analysed and interpreted selected travel articles written by the FAM writers. The findings are then integrated with the analysis of face-to-face interviews with international tourists and then further strengthened with literature. This study addresses the gaps between destination image theories and the depiction of such destination image by travel writers. It is postulated that writers will mould the perception of the destination and therefore enhance the understanding of destination image. Although the present depiction of destination image is very much relevant within most tourism contexts, what is perhaps not considered precisely is whether such interpretation still holds when the image is derived merely from textual data as they are interpreted by FAM writers…